Nitrogen recycling at the Costa Rican subduction zone: The role of incoming plate structure. Issue 1 (December 2017) - Lee, Hyunwoo; Fischer, Tobias; de Moor, J.; Sharp, Zachary; Takahata, Naoto; Sano, Yuji
Abstract Efficient recycling of subducted sedimentary nitrogen (N) back to the atmosphere through arc volcanism has been advocated for the Central America margin while at other locations mass balance considerations and N contents of high pressure metamorphic rocks imply massive addition of subducted N to the mantle and past the zones of arc magma generation. Here, we report new results of N isotope compositions with gas chemistry and noble gas compositions of forearc and arc front springs in Costa Rica to show that the structure of the incoming plate has a profound effect on the extent of N subduction into the mantle. N isotope compositions of emitted arc gases (9–11 N°) imply less subducted pelagic sediment contribution compared to farther north. The N isotope compositions (δ15 N = −4.4 to 1.6‰) of forearc springs at 9–11 N° are consistent with previously reported values in volcanic centers (δ15 N = −3.0 to 1.9‰). We advocate that subduction erosion enhanced by abundant seamount subduction at 9–11 N° introduces overlying forearc crustal materials into the Costa Rican subduction zone, releasing fluids with lighter N isotope signatures. This process supports the recycling of heavier N into the deep mantle in this section of the Central America margin.